Lay views in Southern France of the acceptability of refusing to provide treatment because of alleged futility - María Teresa Muñoz Sastre; Paul Clay Sorum; Etienne Mullet (BMC Medical Ethics)
Abstract Aim To carry out a detailed study of existing positions in the French public of the acceptability of refusing treatment because of alleged futility, and to try to link these to people’s age, gender, and religious practice. Method 248 lay participants living in southern France were presented with 16 brief vignettes depicting a cancer patient at the end of life who asks his doctor to administer a new cancer treatment he has heard about. Considering that this treatment is futile in the patient’s case, the doctor refuses to prescribe it. The vignettes were composed by systematically varying the level of four factors: likelihood of a positive effect, painfulness to the patient of the treatment, cost of the treatment, and attitude of the family. Results Five main positions were identified. For 10%, refusing treatment was almost never acceptable. 35% judged acceptability in line with the level of painfulness. 19% judged acceptability consistent with an interaction between the painfulness of treatment and likelihood of positive effect. For 30% it was either almost always acceptable or always acceptable. 5% did not take a position. Conclusion A range of positions regarding the acceptability of refusing to provide treatment on the basis of perceived futility was observed. These positions have been analyzed in terms of what physicians and medical ethicists would see as the four principles of medical ethics. This description of lay people’s positions in terms of the principles of medical ethics present clinicians with a conceptual tool to improve communication and shared decision making.